Violencia en la Ciudad de México. Expresiones, desafíos y reflexiones - Ramírez Hernández, Cinthia Maday (Archivos de criminología, seguridad privada y criminalística, 2021)
Daily criminal acts are recorded in Mexico City, expressions of violence that violate personal and social security. The urgency to address the phenomenon of criminality is a priority. Some violent facts are mentioned here and suggestions are made for prevention